Hidradenitis suppurativa and daily lifestyle - Natsuko Saito-Sasaki; Yu Sawada (Frontiers in Immunology)
Hidradenitis suppurativa (HS) is a chronic, relapsing inflammatory skin disorder that significantly impairs quality of life. While its pathogenesis involves genetic, immunologic, and environmental components, emerging evidence highlights the substantial impact of modifiable lifestyle factors on disease onset and progression. This review summarizes the current understanding of how lifestyle-related elements interact with the inflammatory milieu in HS. Beneficial factors, such as short-chain fatty acids (SCFAs), omega-3 fatty acids, and vitamin D, play a protective role by suppressing proinflammatory cytokines, enhancing antimicrobial responses, and promoting the growth of beneficial gut microbiota. Diets rich in vegetables, fruits, chicken, and fish are supportive in maintaining immune balance. Conversely, detrimental factors, including smoking, alcohol consumption, obesity, and sleep disorders, are associated with heightened inflammatory responses, increased disease severity, and higher recurrence rates. Understanding these lifestyle-related influences provides a foundation for non-pharmacologic, adjunctive interventions aimed at mitigating disease burden. Comprehensive management of HS should therefore include lifestyle modification as a key component to improve patient outcomes.